Bridging the Digital Divide with Spirituality: Social Commerce and Sharia Marketing Ethics among Rural Culinary MSMEs - Anisa Fitri; Mufti Fiandi; Riduwansah (CV. Era Digital Nusantara, 2026)
Digital transformation in rural areas is frequently confronted with the characteristics of agrarian communities and infrastructural limitations. This study aims to analyze the contribution of digital marketing strategies toward increasing the revenue of culinary MSMEs in Mekarsari Village, map out the structural obstacles faced, and evaluate the alignment of these digital business operations with the principles of Sharia Marketing Ethics. Utilizing a qualitative approach with a descriptive-analytical design, data were gathered through in-depth interviews with three key informants, social media observations, and source triangulation. The results indicate that the adoption of simple social media platforms (WhatsApp and Facebook) significantly increased self-reported estimated monthly net revenue by IDR 2,500,000 to IDR 5,000,000 through the optimization of hyper-local social network effects and communal bulk orders. However, this implementation remains suboptimal due to structural constraints such as internet signal instability, low digital literacy, and a lack of formal training. From an Islamic economic perspective, the digital marketing activities of these business actors have internalized the values of siddiq, amanah, tabligh, and fathanah. Nonetheless, a gap persists within the formal-legality dimension, as none of the MSMEs possess an official Halal Certification from BPJPH. Theoretically, this study offers a novel contribution by bridging the gap between basic technology adoption and spiritual values. It extends the Digital Empowerment Theory by demonstrating that low-complexity social commerce, when embedded in strong rural social capital, effectively drives micro-level economic resilience. Furthermore, it enriches Islamic marketing literature by conceptualizing how Sharia ethics operate substantively in informal digital ecosystems before formal halal institutionalization. Practically, this study implies the importance of local government synergy in strengthening digital literacy and facilitating halal legality to foster spirituality-based rural economic sustainability.